Dividend Policy Impact of Free Cash Flow, Capital Structure and Return on Assets With Company Size As a Control Variable - Dede Hertina; Yana Hendayana; Ivan Gumilar Sambas Putra; Tasya Nafila (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background:Dividend policy decisions are influenced by factors such as free cash flow, capital structure, and return on assets, with company size acting as a control variable. Purpose: The aim of this research is to determine the influence of Free Cash Flow, debt to equity ratio and Return on Assets on company size in banking companies before and after the Covid 19 pandemicDesign/methodology/approach: This research uses a descriptive method, namely research procedures or problem solving that are investigated by describing the subjects or objects used in the form of people, institutions, society, and others.Findings/Results: The results show that free cash flow had a positive and insignificant effect, the debt-to-equity ratio had a negative and significant effect, return on assets had a negative effect on company size before the Covid-19 pandemic, and there was a significant increase in dividend policy before and during the Covid-19 pandemic.Conclusion: The implications of the results of this study for the dividend policy impact of free cash flow, capital structure and return on assets with company size as a control variable Originality/value (State of the art): Companies with higher free cash flows tend to pay out more dividends, whereas a well-managed capital structure and strong return on assets can also support dividend payouts. Company size, as a control variable, helps isolate the effect of these financial factors on dividend policy, ensuring that the results aren't skewed by the size of the firm. Keywords:  company size, debt to equity, dividend policy, free cash flow, return on assets